Outcome for the group SL(2,57) - Niran Sabah Jasim; Mohammed Salah Aldeen Zidan; Azza I.M.S. Abu-Shams; Ahmad Issa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The set of all (n×n) non-singular matrices over the field F this set forms a group under the operation of matrix multiplication. This group is called the general linear group of dimension over the field F, denoted by . The determinant of these matrices is a homomorphism from into F* and the kernel of this homomorphism was the special linear group and denoted by Thus is the subgroup of which contains all matrices of determinant one. The rational valued characters of the rational representations written as a linear combination of the induced characters for the groups discuss in this paper and find the Artin indicator for this group after study the rational valued characters of the rational representations and the induced characters.